Combined Mechanical–Chemical Weed Control Methods in Post-Emergence Strategy Result in High Weed Control Efficacy in Sugar Beet - Jakob Berg; Helmut Ring; Heinz Bernhardt (Agronomy)
Against the backdrop of increasing herbicide resistance and societal and political objectives for reducing plant protection products, combinations of mechanical and herbicide weed control methods are gaining importance. In row crops such as sugar beet, the use of mechanical hoeing between crop rows (interrow) combined with band spraying of herbicides within rows (intrarow) can lead to significant herbicide savings compared to standard broadcast herbicide applications. However, effective weed control remains crucial. In this study, a two-year field experiment was conducted to evaluate different combinations of band spraying, mechanical hoeing, and broadcast spraying in post-emergence weed control applications in sugar beet. The weed control efficacy of each treatment was assessed relative to an untreated control using weed counting to determine absolute weed density and image analysis to quantify weed cover. Compared to the untreated control, total weed control efficiencies of up to 90.8% (weed counting) and 99.5% (image analysis) were achieved. In comparison to three consecutive broadcast herbicide applications, the mechanical–chemical combinations resulted in a similar or even superior weed control efficacy while enabling herbicide reductions of up to 65.59%. These results highlight the valuable potential of mechanical–chemical weed control combinations for herbicide-reduced weed management within post-emergence application systems in sugar beet. They represent a key tool in the context of integrated weed management (IWM).